Pengaruh Pembelajaran Sains Terhadap Perkembangan Fisik Motorik Pada Anak Kelompok B Di TK Desa Kateguhan 02 Kabupaten Sukoharjo Tahun Ajaran 2016/2017 - Esti Wibowo, Andryani, Sri Slamet, M.Hum., M.Pd (2017)
ABSTRACT The purpose of this study is to determine the effect of the physical motor learning in group B TK Desa Kateguhan 02 kabupaten Sukoharjo in the academic year of 2016/2017. This research method was quantitative method, using a type of experimental research study design with pre-experimental design. Pre-experimental research design was to form one group pretest-posttest design. This research was conducted in TK Desa Kateguhan 02 Kabupaten Sukoharjo. Subjects in this study were the group B TK Desa Kateguhan 02 with the number of 11 children. The data collection techniques in this research was conducted through observation, namely nonparticipant observation. Data analysis techniques in this study using T-test with SPSS 16.0 for Windows. The results of data analysis using ttest obtained tarithmetic - 7,621 ≤ -ttable -1,8125 then H0 rejected and Ha accepted which it means that there is the influence of science learning toward the physical motor of children TK Desa Kateguhan 02 Kabupaten Sukoharjo. Keywords: Learning science, physical motor